Assessment of oral manifestations of patients with renal failure undergoing hemodialysis by serum and salivary biomarkers - Abdulla, Dr. Hajer Ibrahem; Al-Kotany, Dr. Dr.Munir Y.; Mahdi, Dr.Karar Abdulzahra (Mustansiria Dental Journal, 2018)
Background: Renal failure refers to a condition where the kidneys lose their normal functionality. Patients with end stage renal disease (ESRD) have to undergo hemodialysis (HD), With impaired renal function, a decreased glomerular filtration rate (GFR), and the accumulation and retention of various products of renal failure, the oral cavity may show a variety of changes as the body progresses through an azotemic to a uremic state. The general dentist should be able to recognize these oral symptoms as part of the patient’s systemic disease and not as an isolated occurrence. Aims of the study: To evaluate the biochemical properties of the saliva and Assessment of oral manifestations in patients with chronic renal failure undergoing hemodialysis. Patients and methods: Spectrophotometer was used for measuring serum and salivary calcium, phosphorous, urea and creatinine in thirty three hemodialysis patients and twenty two control healthy subjects . Salivary PH, Gingival index and salivary buffering capacity was also recorded. Results and discussion: All serum and salivary biomarkers (calcium, phosphorous, urea and creatinine) were significantly changed in hemodialysis patients (calcium decreased while the others increased).Also salivary PH and buffering capacity were significantly increased in hemodialysis patients. Gingival index also increased, and the oral manifestations that was recorded include: dry mouth (n=21), uremic odor (n=20) , bad taste (n=17) , burning sensation (n=14) , coated tongue (n=10) ,pale mucosa ( n=5) petechia (n=3), fissured tongue (n=3). Conclusions: there was differences in salivary parameters between hemodialysis patients and control group and the salivary variables was correlated too serum variables , many oral manifestations found to be in hemodialysis patients.